A cyanide-free and ammonium-free high corrosion and wear resistance composite zinc plating solution and a preparation method thereof
Patent Information
- Application Number
- CN202611229738.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-09
AI Technical Summary
[0020]针对现有无氰镀锌含铵致废水总氮超标、镀层综合性能偏低、强碱腐蚀精密工件、单一络合剂螯合容量不足、合金组分沉积不均匀等多重痛点,提供一种全无氰、零铵根、pH5.0~6.0弱酸性复合电镀锌镀液;全程不使用氰化物、各类铵盐,依托葡萄糖酸钠-酒石酸钾钠-三乙醇胺三元复合协同体系调控金属离子沉积,搭配锌镍钴三元合金改性组分、硅烷偶联剂改性纳米耐磨颗粒,同步实现源头减污、镀层高耐蚀、高耐磨,契合国家节能环保产业扶持政策导向
(1)彻底消除氰化物安全污染风险,环保升级优势突出
Smart Images

Figure CN122879772A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of green anti-corrosion electroplating technology for metal surfaces, specifically involving a cyanide-free, zero-ammonia weakly acidic composite electroplating zinc bath and its standardized preparation and electroplating process, which is suitable for long-term anti-corrosion and wear-resistant surface treatment of engineering machinery, precision hardware parts, and new energy steel components.
[0002] The plating solution system of this invention does not add cyanide or various ammonium compounds such as ammonium chloride, ammonium sulfate, ammonium sulfamate, and ammonia throughout the entire process, thus eliminating the risk of cyanide toxicity and the problem of excessive total nitrogen in electroplating wastewater from the source. It belongs to the energy-saving, environmentally friendly, and clean new material surface treatment technology, which is in line with the industry's green upgrading policy. Background Technology
[0003] Electroplating zinc is the most commonly used anti-corrosion surface treatment process for steel substrates, and it is widely used in many fields such as engineering machinery, hardware products, and new energy equipment. At present, industrialized cyanide-free zinc plating processes are mainly divided into two mainstream systems: alkaline zincate cyanide-free zinc plating and acidic chloride zinc plating. Both of these conventional processes have environmental defects and shortcomings in coating performance, making it difficult to simultaneously meet the multiple high-end application requirements of precision workpiece adaptation, high corrosion resistance, high wear resistance, and clean mass production.
[0004] Route 1: Alkaline cyanide-free pure zinc plating process (corresponding reference document CN102304731A) CN102304731A discloses a wide-temperature, wide-current, high-brightness cyanide-free alkaline zinc plating process, which is a basic cyanide-free zinc plating technology solution commonly used in the industry. The core components of the plating bath include 8~12g / L zinc oxide, 120~140g / L sodium hydroxide, a special composite brightener, and a halogenated aminourea polymer, suitable for 0.5~8.0A / dm³. 2 The cathode current density and operating temperature range are 5~45℃. This process uses a highly concentrated sodium hydroxide to construct a strongly alkaline system with a pH > 12, which can only achieve pure zinc coating deposition. It does not introduce alloying modifiers or nano-wear-resistant reinforcing fillers, and thus has significant technical limitations.
[0005] 1. Insufficient overall performance of the coating: This process can only produce pure zinc coatings, lacking the grain refinement and grain boundary filling modification mechanism of nickel and cobalt elements. The micro-grains of the coating are coarse and loose, the coating thickness uniformity in high and low current areas is poor, and the neutral salt spray resistance life is limited. At the same time, without the introduction of nano hard wear-resistant fillers, the coating hardness and wear resistance are low, which cannot be adapted to high-intensity and high-wear industrial application conditions.
[0006] 2. Poor compatibility with precision workpieces: The high-concentration strong alkali system is highly corrosive and can easily cause corrosion and deformation damage to thin-walled and easily deformable precision steel parts. It is only suitable for processing conventional thick-walled workpieces, and its application scenarios are severely limited.
[0007] 3. Limited plating solution control capability: The system lacks a multi-component complex synergistic control structure, resulting in generally poor metal ion deposition stability. The uniformity of coating crystallization and the ability to disperse deep plating of blind hole workpieces are difficult to meet the processing requirements of high-end complex workpieces.
[0008] Route 2: Acidic chloride zinc plating process (a well-known and commonly used technology in the industry) Traditional acidic potassium chloride zinc plating is a mature mass-production process in the field. Typical industry formulations use 40-70 g / L zinc chloride and 180-220 g / L ammonium chloride as core components, combined with boric acid to create a buffer system, maintaining a stable working pH of 4.5-6.0. This process offers advantages such as high current efficiency, low risk of hydrogen embrittlement of workpieces, and good coating brightness, and is widely used in the mass production of ordinary hardware parts. However, it has inherent environmental shortcomings and performance bottlenecks, making it unsuitable for the current demands of clean and high-performance industrial development.
[0009] 1. The risk of excessive total nitrogen in wastewater is prominent and the treatment cost is high: This process uses a high ratio of ammonium chloride as the core conductive and complexing component. The system is severely enriched with ammonium ions, and the total nitrogen content of the electroplating raw water far exceeds the limit of GB 21900-2008 "Electroplating Pollutant Discharge Standard". It cannot be discharged directly in compliance with the standard and requires multi-stage denitrification equipment such as stripping, breakpoint chlorination, and biochemical denitrification, which greatly increases the equipment investment and operation and maintenance costs.
[0010] 2. Wastewater treatment is difficult and solid waste output is large: Zinc ions can combine with ammonium ions in the system to form highly stable zinc-ammonia complexes. Conventional alkaline flocculation and precipitation processes cannot effectively remove zinc ions, so a complex-breaking pretreatment process must be added. The process is complicated, the amount of reagents consumed is large, the output of electroplating sludge and hazardous waste is significantly increased, and the environmental management pressure on enterprises is high.
[0011] 3. Weak coating performance and limited application range: This process can only produce pure zinc coatings, without alloy corrosion-resistant modification and nano wear-resistant strengthening structure. The neutral salt spray life of the coating is generally less than 80 hours, and the wear resistance and impact resistance are poor. At the same time, the deep coating dispersion ability of the plating solution is limited, and the adaptability to complex structural workpieces such as blind holes and irregular pipe parts is poor. It cannot meet the long-term protection and wear-resistant working conditions requirements of high-end engineering machinery and new energy parts.
[0012] Route 3: Alkaline cyanide-free zinc-nickel binary alloy zinc plating process (corresponding reference document CN105350037A) CN105350037A discloses an alkaline, cyanide-free zinc-nickel alloy electroplating process, belonging to a strong-base zincate system. This process employs a main-auxiliary composite complexing system, using hydantoin and its derivatives as the main ligand, and can be combined with auxiliary ligands such as triethanolamine, potassium sodium tartrate, and ammonium citrate. The plating bath is prepared with zinc sulfate, nickel sulfate, and potassium carbonate to achieve co-deposition of the zinc-nickel binary alloy. This process requires controlling the nickel content of the plating layer to 10-16 wt.%, relying on the high nickel component to generate a single γ-Ni5Zn.21 Intermetallic compounds can improve corrosion resistance, but their technical system has many inherent limitations.
[0013] 1. Corrosion resistance depends on high nickel ratio and has poor economic efficiency in mass production: This process must rely on a high nickel content of 10~16wt.% to stably generate a γ phase structure in order to achieve high corrosion resistance. High nickel raw materials significantly increase production costs. Moreover, the system does not introduce a cobalt element grain boundary modification mechanism, and has no grain refinement or defect sealing function. The path to improve corrosion resistance is singular and highly dependent.
[0014] 2. Insufficient compatibility of the complexation system and poor coating uniformity: This patent uses hydantoin derivatives as the core complexation system, but fails to construct a synergistic complexation architecture of sodium gluconate-sodium potassium tartrate-triethanolamine tri-organic acid. Furthermore, the amount of potassium carbonate added is as high as 5~435g / L, resulting in a large difference in metal ion deposition potential, which easily leads to uneven distribution of coating components and poor deposition consistency.
[0015] 3. Lack of wear-resistant reinforcement structure and weak mechanical properties: This process does not introduce nano-hard wear-resistant particles such as alumina and silicon carbide, and only relies on alloy components to improve the basic corrosion resistance. The coating hardness and wear resistance are insufficient, making it difficult to adapt to the high-intensity wear-resistant working conditions of high-end equipment.
[0016] 4. Dual defects in environmental protection and precision compatibility: The system as a whole is strongly alkaline with a pH of 7~11, which can easily corrode thin-walled precision parts and has poor compatibility with precision workpieces; at the same time, the auxiliary complexing agent can include ammonium-containing substances such as ammonium citrate and ammonium acetate, which poses a potential environmental risk of introducing ammonium ions and causing the total nitrogen in the wastewater to exceed the standard.
[0017] Existing technological biases and industry challenges: The standard reduction potentials of zinc, nickel, and cobalt metal ions differ significantly, making it difficult to control the uniform co-deposition of ternary alloys. Zinc ions readily precipitate and form a zinc hydroxide passivation film, inhibiting the reduction and deposition of nickel and cobalt ions. Currently, the mainstream technical solutions for improving the corrosion resistance of zinc-based alloys all rely on high nickel ratio designs, generally requiring a nickel content of 8-15 wt.% in the coating.
[0018] However, this mainstream technical solution has an unavoidable drawback: the preparation systems of high-nickel γ-phase alloys are all in strongly alkaline environments, which will severely corrode thin-walled, precision, and easily deformable workpieces, making it unsuitable for the electroplating requirements of precision parts. This has led to an industry technical bias that "high corrosion resistance requires strong alkali, and strong alkali is unsuitable for precision parts." At the same time, existing nanocomposite zinc plating technologies mostly rely on strongly alkaline zincate systems. Nanoparticles have poor dispersion stability in strongly alkaline environments and are prone to agglomeration and sedimentation, making it difficult to simultaneously achieve wear-resistant coating enhancement and stable mass production.
[0019] Domestic regulations such as the "Standard Conditions for the Electroplating Industry," the "Guiding Opinions on Comprehensive Prevention and Control of Heavy Metal Pollution," and Hebei Province's clean production control policies for the electroplating industry have phased out and restricted the elimination of high-pollution cyanide zinc plating and high-ammonium acid zinc plating production lines. The existing three mainstream processes—alkaline pure zinc plating, alkaline zinc-nickel binary alloy zinc plating, and high-ammonium acid zinc plating—cannot simultaneously meet the multiple industrial demands for cyanide-free and zero-ammonium plating, weak acid plating that does not corrode precision workpieces, high corrosion resistance of low-nickel ternary alloys, and high wear resistance of nanoparticle composites. There is a significant technological gap in the industry's clean and high-performance upgrades, necessitating a new green composite electroplating system to replace traditional outdated processes. Summary of the Invention
[0020] Addressing multiple pain points of existing cyanide-free zinc plating solutions, such as excessive total nitrogen in wastewater due to ammonium content, low overall coating performance, strong alkali corrosion of precision workpieces, insufficient chelating capacity of single complexing agents, and uneven deposition of alloy components, this invention provides a cyanide-free, ammonium-free, pH 5.0–6.0 weakly acidic composite electroplating zinc bath. It avoids the use of cyanides and various ammonium salts throughout the process, relying on a ternary composite synergistic system of sodium gluconate-sodium potassium tartrate-triethanolamine to regulate metal ion deposition. Combined with zinc-nickel-cobalt ternary alloy modified components and silane coupling agent-modified nano-wear-resistant particles, it simultaneously achieves pollution reduction at the source, high corrosion resistance, and high wear resistance in the coating, aligning with national energy conservation and environmental protection industry support policies.
[0021] Technical solution A cyanide-free, ammonium-free, highly corrosion-resistant and wear-resistant composite electroplating zinc plating solution (per liter of deionized water solution)
[0022] Key limitations: The plating solution contains no cyanide, ammonium chloride, ammonium sulfate, ammonium sulfamate, ammonia, or any other ammonium salts throughout the entire plating process; the pH of the plating solution is stably controlled between 5.0 and 6.0.
[0023] Standardized preparation method of plating solution Step 1: Prepare the buffer base solution Add citric acid and potassium citrate to deionized water with a conductivity ≤10μS / cm, and stir at 40-50℃ until completely dissolved to obtain a stable buffer base solution. Step 2: Blending the ternary organic complex system Sodium gluconate, potassium sodium tartrate, and triethanolamine were added sequentially and stirred at high speed for 30 minutes to form a uniform and stable multi-component complex premix. Step 3: Dissolve the main metal salt and alloy modifying components Zinc chloride, nickel sulfate, and cobalt sulfate were added slowly in portions, with continuous stirring until all metal salts were completely dissolved. The system solution was clear and transparent, without turbidity or suspended solids. This buffer pH range was verified by multiple examples, and no hydroxide precipitates were formed during the entire metal salt dissolution process. Step 4: Pretreatment and dispersion of nano-wear-resistant particles Nano-alumina and silicon carbide powders are first modified by soaking in silane coupling agent ethanol solution, washed with water, and dried at low temperature; the modified powders are then added to the plating solution and simultaneously ultrasonically dispersed for 20 minutes with mechanical stirring, in conjunction with polyether-modified siloxane dispersing aids to prevent powder agglomeration and sedimentation. Step 5: Add conductive salt and brightening dispersant additive Add potassium chloride and polyether-modified siloxane brightening dispersant, and stir continuously for 40 minutes to mix evenly; Step 6: pH calibration and precision filtration The pH of the plating solution was adjusted to 5.0–6.0 using dilute potassium hydroxide and dilute hydrochloric acid. Trace impurities were removed by filtration through a 5μm precision filter. The solution was then allowed to stand at room temperature for 12 hours to mature, resulting in the final composite electroplating solution.
[0024] Matching electroplating application processes 1. Workpiece pretreatment process: dilute alkali electrolysis degreasing → multi-stage pure water rinsing → dilute weak acid activation → final pure water rinsing. 2. Pure zinc plate is selected as the anode, and the steel workpiece to be plated is used as the cathode. The distance between the anode and cathode is fixed, and the ratio of the anode to cathode area is 1.2:1. 3. Electroplating process parameters: plating bath temperature 15~45℃, cathode current density 0.8~6A / dm³ 2 The electroplating time is matched with the target coating thickness; 4. After electroplating, trivalent chromium passivation or chromium-free passivation sealing treatment is performed. After passivation, multi-stage pure water rinsing is carried out to significantly reduce the amount of wastewater generated at the end.
[0025] Beneficial effects (1) Completely eliminates the safety pollution risk of cyanide, and has outstanding advantages in environmental protection upgrade. The formula contains no cyanide components throughout the entire process, eliminating the risk of hydrogen cyanide volatilization during electroplating production. It also eliminates the need for dedicated storage facilities for highly toxic chemicals and explosion-proof and poison-proof control facilities. Furthermore, it generates no cyanide-containing wastewater or hazardous waste, saving the entire wastewater treatment process of cyanide complex breaking and detoxification. This significantly reduces the operating costs of hazardous waste disposal and wastewater treatment, aligning with the national policy of phasing out cyanide electroplating and promoting cleaner production across the entire industry.
[0026] (2) Zero ammonium system completely eliminates the problem of excessive total nitrogen in electroplating wastewater. No ammonium-based raw materials are added throughout the process, and the total nitrogen in the electroplating raw water is naturally lower than the national wastewater discharge limit, eliminating the need for a separate biochemical denitrification treatment section. According to the pilot production line, compared with the traditional high-ammonium zinc plating process, the 10,000-ton electroplating production line significantly reduces the consumption of wastewater treatment agents and the amount of sludge and hazardous waste generated, saving water and reducing energy consumption. It is a source-based pollution reduction, carbon reduction, energy-saving and environmentally friendly technology.
[0027] (3) The chloride ion content in the system decreased significantly, and the downstream water treatment load decreased. Traditional acidic potassium chloride zinc plating requires 180-220 g / L of potassium chloride, while this invention uses only 60-90 g / L of potassium chloride combined with a low amount of zinc chloride. Through precise calculation, the total chloride ion molar concentration of this invention is reduced by more than 36% compared to the traditional process. The water treatment membrane filtration and neutralization sedimentation loads are reduced simultaneously, and the output of saline sludge solid waste is significantly reduced.
[0028] Innovative Advantages of Coating and Process Performance (1) Citric acid-potassium citrate stable buffer system, ternary mixed ligands synergistically enhance deep plating capability The citric acid-potassium citrate buffer effectively covers the target pH range of 5.0-6.0, with sufficient buffering capacity and minimal pH fluctuations during long-term electroplating operation. Sodium gluconate and potassium sodium tartrate act as the main complexing agents to stably chelate metal ions, while triethanolamine acts as an auxiliary component to improve interfacial wettability and promote anodic dissolution. Under the synergistic effect of the ternary compound, the Hull bath thickness ratio can reach 0.74-0.78, and the deep plating dispersion ability is close to that of traditional cyanide zinc plating. It can be adapted to complex blind holes, irregularly shaped pipes, and thin-walled precision workpieces. The weakly acidic system will not corrode precision steel thin-walled parts.
[0029] (2) Low-nickel zinc-nickel cobalt ternary alloy + dispersed cobalt grain boundary filler, combined with two-component nanoparticle composite, breaks through the industry's technical prejudice that high corrosion resistance must be high nickel. As is well known in the art, the high corrosion resistance of zinc-nickel alloys relies on the formation of a large amount of stable γ-Ni5Zn within the coating. 21 The intermetallic compound phase is stably formed when the nickel content of the coating reaches 8-15 wt.%. Referring to authoritative research and example data disclosed in prior art document CN105350037A, conventional zinc-nickel alloy systems require a nickel content of 12.39-13.94 wt.% to stably form a single γ-phase structure, achieving excellent corrosion resistance. This corresponds to a positive shift in corrosion potential and a significant reduction in corrosion current density. Currently, mainstream high-corrosion-resistant zinc-nickel alloy processes in the industry all follow this technical logic, but they have inherent drawbacks: the process systems that can stably generate highly corrosion-resistant γ-phases are all in strongly alkaline environments, which severely corrode thin-walled, precision, and easily deformable workpieces, making them unsuitable for the electroplating requirements of precision parts. Furthermore, high-nickel raw materials significantly increase production costs, resulting in poor economic efficiency for mass production. This has led to a long-standing technical bias in the field that "high corrosion resistance necessarily requires high nickel, and high nickel necessarily requires strong alkali."
[0030] This invention creatively breaks through the aforementioned industry consensus, completely abandoning the technical dependence on high nickel ratios of 8-15 wt.% and γ-phase alloy structures. Within a low-nickel, low-cost ratio range of only 2.1 wt.% to 3.5 wt.%, it achieves ultra-high corrosion resistance through multi-mechanism coupling and synergy: First, trace amounts of cobalt are uniformly dispersed and fill the grain boundaries of the coating, refining the grains, sealing microscopic defects at the grain boundaries, and blocking the conduction channels of the corrosion galvanic cell. Second, the ternary metal components of zinc, nickel, and cobalt synergistically generate a continuous, dense, and low-porosity multi-component composite passivation film at the corrosion interface, which significantly improves the barrier ability against chloride ion corrosion media compared to traditional binary zinc-nickel passivation films. Third, silane-modified alumina / silicon carbide nanoparticles are uniformly embedded in the coating matrix, further enhancing the density and mechanical stability of the coating structure through the dual effects of grain refinement and physical barrier strengthening.
[0031] Through the synergistic effect of the aforementioned multiple innovative mechanisms, this invention can stably achieve an ultra-long neutral salt spray protection duration of 163~218 hours without relying on a high-nickel γ-phase structure, achieving superior technical effects that exceed conventional technical understanding in the field and cannot be predicted by existing technologies. Simultaneously, this invention employs a weakly acidic system, completely avoiding the defects of strong alkali corrosion on precision workpieces, and balancing workpiece compatibility, high corrosion resistance, and mass production economics. The polyether-modified siloxane bright dispersant possesses dual core functions of grain refinement and nanoparticle dispersion, effectively solving the industry problem of easy agglomeration and sedimentation of nanoparticles in weakly acidic systems, ensuring long-term stable mass production operation of the plating solution. Attached Figure Description Appendix Figure 1 This is a flowchart of the standardized preparation method of the plating solution of the present invention. Detailed Implementation
[0032] All embodiments uniformly control the coating thickness to 8±1μm; after the plating solution is prepared, it is allowed to stand for 72h, and the plating solution is clear without precipitation and the nanoparticles do not stratify and settle; uniform testing items: EDX energy dispersive spectroscopy alloy composition, neutral salt spray NSS, Taber wear resistance, Vickers microhardness HV, Hull tank deep plating dispersion ability, and nanoparticle settling rate. All test data can be repeatedly verified.
[0033] Example 1 (Intermediate Preferred Ratio) Per liter of plating solution: 32 g / L zinc chloride, 52 g / L ternary organic complexing agent, 75 g / L potassium chloride, 4 g / L nickel sulfate, 2.5 g / L cobalt sulfate, 8 g / L KH-560 silane-modified nano-alumina / silicon carbide powder (mass ratio 1:1), 2.2 g / L polyether-modified siloxane, 12 g / L citric acid-potassium citrate buffer, with the balance being deionized water with conductivity ≤10 μS / cm; pH=5.5. This invention breaks through the industry's mainstream high-nickel corrosion-resistant technology bias, eliminating the need for an 8-15 wt.% high nickel ratio and γ-phase intermetallic compound support. Through a coupling mechanism of cobalt element dispersed grain boundary filling, nanoparticle composite reinforcement, and multi-component complex synergistic passivation, it achieves ultra-high corrosion resistance in a low-nickel range of only 2.1-3.5 wt.%, achieving superior technical results beyond conventional industry understanding.
[0034] Electroplating parameters: Temperature 30℃, Current density 2.5A / dm³ 2 Electroplating for 25 minutes resulted in a coating thickness of 8 μm. Actual performance: 1. No white rust was observed after 192 hours of neutral salt spray testing; the coating microhardness was HV620; and the Taber wear resistance was reduced by 41% compared to the control. 2. EDX mass fraction: Zn 95.4 wt.%, Ni 3.1 wt.%, Co 1.5 wt.%, ternary alloy uniformly co-deposited, with no preferential segregation of zinc; 3. Hull bath deep plating test (current 1A, electroplating 10min): far cathode / near cathode plating thickness ratio = 0.78, which is significantly better than the traditional alkaline zincate zinc plating of 0.55; 4. The modified nanoparticles settled at a rate of 0.32 mm / h after standing for 72 hours, with no visible stratification.
[0035] Example 2 (Upper Limit Ratio of Formulation) Per liter of plating solution: 45 g / L zinc chloride, 70 g / L ternary organic complexing agent, 90 g / L potassium chloride, 6 g / L nickel sulfate, 4 g / L cobalt sulfate, 12 g / L modified nanoparticles (1:1), 3.5 g / L brightening dispersant, 16 g / L buffer, balance deionized water; pH=6.0.
[0036] Actual performance: 218h neutral salt spray test, HV675, wear resistance reduced by 44%; coating Ni 3.5wt.%, Co 1.6wt.%; Hull tank thickness ratio 0.76; powder settling rate 0.35mm / h.
[0037] Example 3 (Formulation lower limit boundary ratio) Per liter of plating solution: 25 g / L zinc chloride, 35 g / L ternary organic complexing agent, 60 g / L potassium chloride, 2 g / L nickel sulfate, 1 g / L cobalt sulfate, 4 g / L modified nanoparticles (1:1), 1.2 g / L brightening dispersant, 8 g / L buffer, balance deionized water; pH=5.0.
[0038] Actual performance: 163h neutral salt spray test, HV560, wear resistance reduced by 37%; coating composition: Ni 2.1wt.%, Co 0.8wt.%; Hull tank thickness ratio: 0.74; powder settling rate: 0.38mm / h.
[0039] Comparative Example 1 (Reproduction of CN105350037A Traditional Alkaline Cyanide-Free Zinc-Nickel Alloy Process) The inventors completely reproduced the plating solution according to the preferred embodiment in the specific implementation of CN105350037A specification, prepared a standard plating layer with a thickness of 8μm using unified electroplating process parameters, and simultaneously conducted a full set of performance comparison tests. The obtained test data is highly consistent with the performance change trend described in the patent, which can objectively and truthfully reflect the performance shortcomings of the existing alkaline zinc-nickel binary alloy process. The specific test results are as follows: White rust appeared after 72 hours of neutral salt spray, the coating was HV320, and the Taber wear loss was significantly higher than in all embodiments of the present invention; the far / near cathode coating thickness ratio in the Hull tank was only 0.53; the system was strongly alkaline, and the production wastewater must be equipped with a biological denitrification section, resulting in a significantly higher overall water treatment operating cost than the present invention.
Claims
1. A cyanide-free, ammonium-free, highly corrosion-resistant and wear-resistant composite electroplating zinc bath, characterized in that, Each liter of plating solution consists of the following components: The composition includes: zinc chloride 25–45 g / L, ternary organic complexing agent 35–70 g / L, potassium chloride 60–90 g / L, nickel sulfate 2–6 g / L, cobalt sulfate 1–4 g / L, nano-wear-resistant composite particles 4–12 g / L, nonionic brightening filler additive 1.2–3.5 g / L, pH buffer adjuster 8–16 g / L, with the balance being deionized water; the conductivity of the deionized water is ≤10 μS / cm. The ternary organic complex complexing agent is a mixture of sodium gluconate, potassium sodium tartrate, and triethanolamine in a mass ratio of 2:1:
1. The nano-wear-resistant composite particles are a mixture of nano-alumina and nano-silicon carbide powders with a mass ratio of 1:1 to 3:1, and the powders are pretreated with a silane coupling agent for surface modification before use. The nonionic bright filler additive is a polyether-modified siloxane; The pH buffer adjuster is a citrate-potassium citrate buffer system composed of citric acid and potassium citrate. The plating solution is free of cyanide and any ammonium salts throughout the entire process, and the pH of the plating solution is stably controlled between 5.0 and 6.
0.
2. The cyanide-free, ammonium-free, highly corrosion-resistant and wear-resistant composite electroplating zinc bath according to claim 1, characterized in that, The silane coupling agent is KH-560 epoxy silane coupling agent.
3. The cyanide-free, ammonium-free, highly corrosion-resistant and wear-resistant composite electroplating zinc bath according to claim 1, characterized in that, Optimal content of each component per liter of plating solution: Zinc chloride 32g / L, ternary organic complex complexing agent 52g / L, potassium chloride 75g / L, nickel sulfate 4g / L, cobalt sulfate 2.5g / L, KH-560 modified nano wear-resistant composite particles 8g / L, polyether modified siloxane bright dispersant 2.2g / L, citric acid-potassium citrate buffer 12g / L, with the balance being deionized water with a conductivity ≤10μS / cm.
4. A method for preparing the cyanide-free, ammonium-free, highly corrosion-resistant and wear-resistant composite electroplating zinc bath according to claim 1 or 2, characterized in that, Includes the following steps: (1) Preparation of buffer base solution: Add citric acid and potassium citrate to deionized water, stir at 40-50℃ until completely dissolved to obtain buffer base solution; (2) Preparation of the ternary complex system: Sodium gluconate, potassium sodium tartrate and triethanolamine are added in sequence and stirred at high speed for 30 min to form a stable complex premix; (3) Dissolving the main metal salt and alloy components: Add zinc chloride, nickel sulfate and cobalt sulfate slowly in portions, and continue stirring until all metal salts are completely dissolved. The system solution is clear and transparent, without turbidity or solid suspension. (4) Nanoparticle modification and dispersion: Nano-alumina and silicon carbide powders were modified with silane coupling agent ethanol solution, washed and dried with water and then added to the system. They were ultrasonically dispersed for 20 minutes in combination with mechanical stirring. (5) Add conductive salt and brightening dispersant: Add potassium chloride and polyether modified siloxane brightening dispersant, and stir continuously for 40 minutes to mix evenly; (6) pH calibration and precision filtration: Adjust the pH to 5.0-6.0 with dilute potassium hydroxide and dilute hydrochloric acid, filter through 5μm filter material, and mature at room temperature for 12h to obtain the finished composite plating solution.
5. The preparation method according to claim 4, characterized in that, The deionized water used in step (1) has a conductivity of ≤10μS / cm, and the proportions of each component are as described in claim 3.
6. A method for electroplating the cyanide-free, ammonium-free, highly corrosion-resistant and wear-resistant composite electroplating zinc bath as described in claim 1, characterized in that, include: Workpiece pretreatment: dilute alkali electrolysis for degreasing → multi-stage pure water rinsing → dilute weak acid activation → final pure water rinsing; pure zinc plate is used as the anode, and steel workpieces are used as the cathode, with an anode-cathode area ratio of 1.2:1; electroplating process temperature is 15~45℃, and cathode current density is 0.8~6A / dm². 2 After electroplating, a trivalent chromium passivation or chromium-free passivation sealing treatment is performed.
Citation Information
Patent Citations
Wide temperature, wide current and wide brightness type cyanide-free alkaline zinc plating process
CN102304731A
Alkaline non-cyanide zinc plating nickel alloy plating solution and electroplating process thereof
CN105350037A